Biologics in Sjögren's syndrome. (September 2019) - Skarlis, Charalampos; Marketos, Nikolaos; Mavragani, Clio P.
Graphical abstract: Abstract: The use of biologic disease modifying antirheumatic drugs (bDMARDs) in systemic autoimmune diseases such as rheumatoid arthritis and at a lesser extent in lupus, has been well established. In Sjögren's syndrome (SS), despite the shared pathogenetic mechanisms with other autoimmune disorders, traditional immunomodulatory drugs have failed to address the main clinical features of the disease and use of biologics has been limited so far. Over the last years, our better understanding in disease pathogenesis has led to an expansion in the number of clinical trials exploring the effect and safety of biological agents with variable results. In the current review, the effect of targeting key molecular mechanisms involved in SS pathogenesis such as antigen presentation, B and T cell activation and germinal center formation is discussed.